2016
DOI: 10.1103/physreve.94.062307
|View full text |Cite
|
Sign up to set email alerts
|

Critical behavior ofk-core percolation: Numerical studies

Abstract: k-Core percolation has served as a paradigmatic model of discontinuous percolation for a long time. Recently it was revealed that the order parameter of k-core percolation of random networks additionally exhibits critical behavior. Thus k-core percolation exhibits a hybrid phase transition. Unlike the critical behaviors of ordinary percolation that are well understood, those of hybrid percolation transitions have not been thoroughly understood yet. Here, we investigate the critical behavior of k-core percolati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 25 publications
6
29
0
Order By: Relevance
“…This is in line with our analysis of the limit where C → ∞(N ) [2]. There we showed that, rather than recovering standard percolation in this case, we instead recover k-core percolation with k = 2 [10,11,36]. On the other hand, color connectivity can be expressed in terms of variables v Q using Eq.…”
Section: A Critical Behaviorsupporting
confidence: 87%
“…This is in line with our analysis of the limit where C → ∞(N ) [2]. There we showed that, rather than recovering standard percolation in this case, we instead recover k-core percolation with k = 2 [10,11,36]. On the other hand, color connectivity can be expressed in terms of variables v Q using Eq.…”
Section: A Critical Behaviorsupporting
confidence: 87%
“…The values of γ/ν for different values of g are also verified by estimating the average cluster size of all the finite clusters (excluding the spanning cluster) at their respective percolation thresholds. However, there are evidences in some other percolation models such as k-core percolation [36] that the scaling behavior of order parameter fluctuation and that of the average cluster size are not identical.…”
Section: (B)mentioning
confidence: 99%
“…A hybrid phase transition is a discontinuous transition but with criticality. Such a transition occurs in several a) Electronic mail: bkahng@snu.ac.kr complex systems, including cascade failure of interdependent networks 5 , k-core [6][7][8] , cooperative epidemic spreading [9][10][11][12] and synchronization [13][14][15][16][17] . However, a possible hysteresis together with critical behavior in hybrid phase transitions has been rarely reported thus far, even though hysteresis in discontinuous transitions was investigated in explosive synchronization [18][19][20] and percolation [21][22][23][24][25][26][27][28][29] in complex systems.…”
mentioning
confidence: 99%
“…For percolation, hybrid percolation transitions (HPTs) may be classified into two categories: one occurring during the cascade process as in k-core percolation [5][6][7][8][9][10][11][12] , and the other during the cluster merging process [30][31][32] . For the former case, dynamics proceed only in one direction of decreasing occupation probability, and a reverse process may not be well defined, i.e., a cascade cluster aggregation process is hardly imagined.…”
mentioning
confidence: 99%